Laparoscopic Ventral Mesh Fixation in Patients with Pelvic Organ Prolapse - Solmaz Imanova; B. M. Zeynalov; Cihangir Akyol (Faculty of Medicine, Universitas Padjadjaran, 2022)
Pelvic organ prolapse (POP) is a condition with a high incidence rate and often creates difficulties in surgical coloproctology and gynecology. The aim of this study was to evaluate the effectiveness of laparoscopic ventral reticular sacrocolporectopexy and sacrorectopexi in women and men with POP, respectively. This study was conducted at the Educational-Surgical Clinic of Azerbaijan Medical University and Department of Surgery of the Faculty of Medicine of Ankara University (2016-2019) on 21 patients with POP (15 women and 6 men). Results of diagnostics and surgical treatment of POP were studied with preferences towards endoscopic, radiation, and functional methods. The surgical methods used in these patients included laparoscopic fixation methods (sacrocolpopexy, sacrocolporectopexy) of protruding organs (uterus, vaginal vault/vaginal cuff, rectum) and simultaneous vaginal (colporrhaphy, colpolevatoroplasty, vaginal plastic surgery) and proctological surgeries (circulatory resection, hemorrhoidectomy, sphincteroplasty). The findings demonstrated that the most progressive POP mostly occurred in women of premenopausal age and during menopause. Based on the results of the long-term evaluation of the surgical treatment (6-12 months), the rates of recurrence of prolapse and complications were low (up to 4.8% and 9.5%, respectively) with favorable long-term functional results, such as a decrease in the degree of fecal incontinence and constipation, observed in the evaluation. Due to the concomitant weakness of the ligamentous apparatus of the pelvic floor in these patients, there is the need for intra-abdominal apical support of organs. In conclusion, that laparoscopic sacrocolpopexy in women and sacrorectopexy in men are reliable surgical method to treat POP. However, specific skills need to be acquired by both gynecologist and coloproctologist to be able to do these laparoscopic surgery techniques.